Unmanned: Brave New Films' screen intervention into America's drone wars. Issue 1 (1st July 2019) - Howley, Kevin
Drawing on the long history of politically committed documentary, Brave New Films combines traditional and emergent production methods with innovative approaches to online distribution and grassroots exhibition aimed at 'creating media that makes an impact'. In what follows, I argue that Unmanned, Brave New Films' screen intervention into the highly circumscribed debate over drone warfare, opens discursive space for human rights lawyers, international relations experts, and witnesses of drone strikes to alert the American people of the legal, strategic and ethical implications of the targeted killing programme. Whether or not Unmanned effects lasting or substantive policy change is, for present purposes, beside the point. Rather, my principal concern is to demonstrate the film's achievement in subverting the dominant discourse surrounding the precision, accuracy and efficacy of US drone strikes.